King, cities, and elites in Macedonia c. 360-168 BC - Raynor, B (2014)
This thesis investigates the nature of the relationship between cities and king in the late Classical and Hellenistic Macedonian kingdom. It will consider the cities from two main perspectives: the city as a community, and the city as a settlement. Section 1 re-examines the evidence most commonly used to argue for the Macedonian cities gaining substantial autonomy in this period. It will be argued that this evidence has less to tell us about the political autonomy of the Macedonian cities than their 'social relations' with other Greek communities: Macedonian cities engaged in international exchanges which did not represent any challenge to the authority of the monarch, but which could also be used to represent the relationship between king and city as cooperative. Such latitude was balanced, however, by forceful expressions of royal dominance in other arenas. Section 2 considers the position of the cities within the royal economy, and examines how, as a result of the king's monopolisation of Macedonia's resources, and the fact that the Macedonian elite was more interested in advancing their position at court than acting as civic benefactors, the cities were left economically subordinated to the king. Section 3 uses the increasingly abundant archaeological evidence to consider how royal building programmes served to project royal ideology into the localities. Royal palaces, large-scale urban development, and fortifications created an experience of urban space in Macedonia which emphasised the roles of the monarch as guardian, benefactor, and unifying figure. The picture that emerges is of a kingdom of civic communities which were engaged in meaningful exchanges with their peers outside Macedonia, but which were living in large and impressive urban settlements which stood as monuments to the extent and ubiquity of royal authority. Late-Classical and Hellenistic Macedonia was a kingdom of poleis, but that kingdom was first and foremost a royal space.